Makna Konotasi Dalam Lirik Lagu “Berharap Pada Timur” Oleh Salma Salsabil (Kajian Semantik) - Ilham Akbar, Muhammad; Dwi Zahrani, Alyka; Sari Ramdhani, Intan (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study aims to describe the connotative meaning contained in the lyrics of the song 'Berharap pada Timur' by Salma Salsabil, with a focus on semantic analysis. The method used is descriptive qualitative with the technique of listening and writing. The researcher will read and understand all the lyrics of the song carefully and record the findings in the form of a song transcript. The results of the study indicate that the connotative meaning in the lyrics of the song 'Berharap pada Timur' has an implied meaning that refers to a person's feelings in maintaining love amidst limitations and social pressures. This song also reflects sincerity, loyalty, struggle, and hope for a relationship that is carried out secretly. This study found three positive connotative meanings and three negative connotative meanings in the lyrics of the song.